Tandem mass spectrometry reveals the quaternary organization of macromolecular assemblies - Benesch, J; Aquilina, J; Ruotolo, B; Robinson, C; al., E (Elsevier, 2006)
The application of mass spectrometry (MS) to the study of progressively larger and more complex macromolecular assemblies is proving increasingly useful for structural biologists. The scope of this approach has recently been widened through the application of a tandem MS procedure. This two-step technique involves the selection of specific assemblies in the gas phase and inducing their dissociation through collisions with argon atoms. Here, we investigate the mechanism of this process and show that dissociation of subunits from a macromolecular assembly follows a sequential pathway, with the partitioning of charge between the dissociation products governed primarily by their relative surface areas. Using this basis of understanding, we highlight differences in the dissociation pathways of three related macromolecular assemblies and show how these are a direct consequence of changes in both local and global oligomeric organization.